Dayak Desa forest land use system as social capital to acquire forest management rights in West Kalimantan, Indonesia - EMI ROSLINDA (Biodiversitas Journal of Biological Diversity, 2016)
Roslinda E. 2016. Dayak Desa forest land use system as social capital to acquire forest management rights in West Kalimantan, Indonesia. Biodiversitas 17: 177-184. People communities have an important role to play in biodiversity conservation. The ownership of land has often become a constraint on sustainable management of forest. The aim of this study was to explore the management system of forest land use in Dayak Desa in West Kalimantan, Indonesia. Data collection was undertaken through field observation, focus group discussion (FGD, and interviews with the community members. Dayak Desa has a several forest land use systems including tawang semilas, tawang sebesai, tawang mersibung, tawang sepayan, tawang serimbak and bukit rentap protection forest, which each system has its own function and utilization. Regardless of the system’s differences, the forest land use systems have been supporting species diversity such as flora, fauna, and environmental services in Dayak Desa. This species diversity can support Dayak Desa community daily needs, regarding food, clothing, housing and other secondary needs. Forest utilization by Dayak Desa community is suitably paired to what can be produced by the land, which is equipped with their own rules. The role and the rule in managing, utilizing and protecting forest land use are Dayak Desa social capital. These are capital to acquire their rights to manage the forest.